2011
DOI: 10.3892/or.2011.1342
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of the presence of lymphatic vessels immunoreactive for D2-40 and Prox-1 in human pterygium

Abstract: Abstract. Human pterygium is a benign fibrovascular outgrowth of the corneo-conjunctival junction, characterized by tissue remodeling, cellular proliferation, angiogenesis and inflammation. No data are available concerning the presence of lymphatic vessels in this pathological condition. The aim of this study was to evaluate by immunohistochemistry, using antibodies against D2-40, Prox-1 and Ki-67, the presence and the proliferative activity of lymphatic vessels in human pterygium. An increased lymphatic micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In the clinic, it has been long observed that certain ocular diseases, such as pinguecula and pterygium, predominantly affect the nasal side of the ocular surface. Though the exact mechanisms remain unknown, new evidence have confirmed the presence of lymphatic vessels in human pterygium [27]. Our findings that the nasal side is naturally more endowed with lymphatic vessels may explain partly why this side is more prone to pathological disorders.…”
Section: Discussionmentioning
confidence: 61%
“…In the clinic, it has been long observed that certain ocular diseases, such as pinguecula and pterygium, predominantly affect the nasal side of the ocular surface. Though the exact mechanisms remain unknown, new evidence have confirmed the presence of lymphatic vessels in human pterygium [27]. Our findings that the nasal side is naturally more endowed with lymphatic vessels may explain partly why this side is more prone to pathological disorders.…”
Section: Discussionmentioning
confidence: 61%
“…Interleukin (IL)-6, IL-8, and vascular endothelial growth factor (VEGF) are prominent players with downstream effects that can be observed in pterygial tissue. Pterygium is characterized by the occurrence of distinct leukocyte populations (i.e., neutrophils, monocytes, mast cells, and T-lymphocytes) [20–22], (lymph)angiogenesis [3, 23], and a hyperplastic epithelium [3]. Both IL-6 and IL-8 promote the chemotactic recruitment of leukocytes [24, 25] and facilitate their in- and efflux by stimulating the development of an extensive lymphatic and vascular network.…”
Section: Introductionmentioning
confidence: 99%
“…Cimpean et al examined primary pterygium samples using D2-40 immunohistochemistry and reported an increased LMD in human pterygium compared with that in normal conjunctiva [ 29 ]. This report was the first to indicate active lymphangiogenesis in human pterygium.…”
Section: Discussionmentioning
confidence: 99%